Books that saved my life reading for wisdom, solace and pleasure - McGirr, Michael 1961- (The Text Publishing Company, 2018)
Great literature is thrilling. It will feed your hungry mind and take your heart on a journey. It will help you on the wonderful path to one of life's most elusive and hard-won freedoms, freedom from the ego. 'His anecdotes will make you out laugh out loud. If you haven't read any books by him before, seek them out.' Good Reading Here is a book about the sheer joy of living, exploring forty texts that can enrich us in all manner of ways. Some are recent, such as Harry Potter; some ancient, such as Homer and Lao Tzu. There are memoirs (Nelson Mandela), poetry (Les Murray) and many of the world's great novels, from George Eliot's Middlemarch to Toni Morrison's Beloved. This book uses them to muse upon life in all its glorious complexity. Our guide, in entertaining short accounts of personal encounters with these works, is Michael McGirr: schoolteacher and father, reviewer of hundreds of books and lifelong lover of literature. His humour and insight shine through in essays that connect the texts he has selected with each other, and connect us to them
Keywords: Literatur; Erfahrung; Lektüre; Australian; Books and reading; Literature